2022
DOI: 10.1007/s11089-022-01023-1
|View full text |Cite
|
Sign up to set email alerts
|

The Well-Being and Resilience of Canadian Christian Clergy

Abstract: Clergy play significant leadership, educational, and caregiving roles in society. However, burnout is a concern for the clergy profession, those they serve, and their families. Effects include decreased ministry effectiveness, lower sense of personal accomplishment in their role, and negative impacts on quality of family life and relationships. Given these risks, knowledge of the nature of Christian clergy’s current resilience and well-being in Canada may provide valuable intelligence to mitigate these challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This article reports on the findings related to types of adversity clergy reported, arising from the qualitative data collection. Other study findings are reported elsewhere, including the results from the quantitative well-being and resilience scale (Clarke et al, 2022a), findings related to the resources that clergy identified as supporting their resilience (Clarke et al, 2022b), and the Clergy Resilience Model (forthcoming).…”
Section: The Purpose Of This Studymentioning
confidence: 86%
“…This article reports on the findings related to types of adversity clergy reported, arising from the qualitative data collection. Other study findings are reported elsewhere, including the results from the quantitative well-being and resilience scale (Clarke et al, 2022a), findings related to the resources that clergy identified as supporting their resilience (Clarke et al, 2022b), and the Clergy Resilience Model (forthcoming).…”
Section: The Purpose Of This Studymentioning
confidence: 86%